An adenovirus prime/plasmid boost strategy for induction of equipotent immune responses to two dengue virus serotypes - Swaminathan Sathyamangalam; Khanna Navin; Rajendra Pilankatta; Khanam Saima (BMC Biotechnology, 2007)
Abstract Background Dengue is a public health problem of global significance for which there is neither an effective antiviral therapy nor a preventive vaccine. It is a mosquito-borne viral disease, caused by dengue (DEN) viruses, which are members of the Flaviviridae family. There are four closely related serotypes, DEN-1, DEN-2, DEN-3 and DEN-4, each of which is capable of causing disease. As immunity to any one serotype can potentially sensitize an individual to severe disease during exposure to a heterologous serotype, the general consensus is that an effective vaccine should be tetravalent, that is, it must be capable of affording protection against all four serotypes. The current strategy of creating tetravalent vaccine formulations by mixing together four monovalent live attenuated vaccine viruses has revealed the phenomenon of viral interference leading to the manifestation of immune responses biased towards a single serotype. Results This work stems from the emergence of (i) the DEN virus envelope (E) domain III (EDIII) as the most important region of the molecule from a vaccine perspective and (ii) the adenovirus (Ad) as a promising vaccine vector platform. We describe the construction of a recombinant, replication-defective Ad (rAd) vector encoding a chimeric antigen made of in-frame linked EDIIIs of DEN virus serotypes 2 and 4. Using this rAd vector, in conjunction with a plasmid vector encoding the same chimeric bivalent antigen, in a prime-boost strategy, we show that it is possible to elicit equipotent neutralizing and T cell responses specific to both DEN serotypes 2 and 4. Conclusion Our data support the hypothesis that a DEN vaccine targeting more than one serotype may be based on a single DNA-based vector to circumvent viral interference. This work lays the foundation for developing a single Ad vector encoding EDIIIs of all four DEN serotypes to evoke a balanced immune response against each one of them. Thus, this work has implications for the development of safe and effective tetravalent dengue vaccines.